Obesity Indices Could Predict High Apolipoprotein B/Apolipoprotein A1 Ratio in Non-menopausal Indonesian Adult Females - Liong Boy Kurniawan; Martina Rentauli Sihombing; Endy Adnan; Gita Vita Soraya; Tenri Esa; Yuyun Widaningsih; Uleng Bahrun; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Previous researches have demonstrated associations between high obesity indices with increased risk of metabolic and cardiovascular disorders. It has also been established that abnormalities of lipoprotein metabolism have an important role in atherogenesis and that non-menopausal females are protected from atherosclerotic cardiovascular events relative to menopausal females and males. This study aimed to investigate the relationship between obesity indices such as body mass index (BMI), waist circumference (WC), body fat percentage (BF), and visceral fat (VF) with apolipoprotein B/apolipoprotein A1 ratio in non-menopausal Indonesian adult females. A total of 75 non-menopausal Indonesian adult females were included as subjects in this cross-sectional study. Measured indices included BMI, WC, BF, and VF. Measurement of apolipoprotein B and A1 were performed by immunoturbidimetry, followed by calculation of the ratio. A cut-off value of 0.8 was used to define high apolipoprotein B/apolipoprotein A1 ratio. Apolipoprotein B/Apolipoprotein A1 ratio was significantly correlated with BMI (r=0.384, p=0.001), WC (r=0.363, p=0.001), BF (r=0.385, p=0.001), VF (r=0.380, p=0.001). The area under curve of BF (0.754) was slightly larger than BMI (0.722), VF (0.721), and WC (0.686) in predicting high apolipoprotein B/apolipoprotein A1 ratio. A positive significant correlation was observed between obesity indices with the apolipoprotein B/apolipoprotein A1 ratio. Obesity indices could be used to predict high apolipoprotein B/apolipoprotein A1 ratio.